Pravni izzivi na presečišču insolvenčnega prava in prava varstva okolja - Cepec, Jaka (Pravni letopis, 2024)
The article examines legal challenges at the intersection of insolvency law and environmental law. It emphasizes the conflict between the “polluter pays” principle, which mandates that polluters bear the costs of environmental remediation, and the principle of equitable creditor repayment. The paper analyzes the impact of these conflicts on insolvency proceedings, focusing on cases where environmental liabilities of insolvent debtors are transferred to society. A comparative analysis of legal frameworks highlights potential solutions for better alignment of the two fields, including mechanisms such as super-priority status for environmental claims, mandatory financial guarantees, and dedicated environmental remediation funds. An evaluation of Slovenia’s legislation reveals certain deficiencies and inconsistencies, supported by an overview of relevant case law.
Keywords: environmental liability; environmental protection; insolvency; insolvency of the environmental polluter; insolventnost; insolventnost povzročitelja okoljske obremenitve; načelo onesnaževalec plača; okoljska odgovornost; polluter pays principle; varstvo okolja